The influence of muscle action on joint loading during dynamic finger pressing tasks in an open-source modelling environment. (1st January 2014) - MacIntosh, Alexander R.; Vignais, Nicolas; Cocchiarella, David M.; Kociolek, Aaron M.; Keir, Peter J.
Assessing finger joint loading is essential to the prevention of work-related musculoskeletal disorders of the hand and fingers. This study aimed to evaluate the effect of muscle action on joint loading during dynamic finger pressing tasks using an open-source musculoskeletal modelling platform. Eight participants performed submaximal dynamic index finger pressing tasks while maintaining a nominal vertical target force of 10 N. Kinematic and force data were used to develop and assess an inverse dynamics link segment model and a musculoskeletal model. Although musculoskeletal model results for metacarpophalangeal joint compression evaluated statically (34.92 ± 1.53 N) and dynamically (34.80 ± 4.40 N) did not differ, changes in anterior-posterior shear and compression throughout the motions identify where the current open-source model is able to provide valuable insight into the assessment of risk of developing MSD during sub-maximally loaded dynamic pressing tasks.